Analisis Persepsi Wisatawan Mengenai Kualitas Daya Tarik Wisata Permandian Di Kelurahan Kumaligon Kecamatan Biau Kabupaten Buol - Muhammad Nasir Marumu; Ishak Arb. Kaulusan; Ramlawati Ramlawati (Economy Deposit Journal (E-DJ), 2021)
Tourist Attractions in Regency There are quite a lot of tourist attractions in Buol Regency, but until now the arrangement or management has not been overall for natural tourism objects in Buol Regency, one of which is the Kumaligon Baths. . Kumaligon Baths is an area located in Kumaligon Village, Biau District, Buol Regency which is famous for its clear, cool water and hilly areas that are so beautiful to look at, and access to a location that is so close to the center of Buol city, especially in the Biau sub-district. . The purpose of our research is to identify and describe the perception of tourists regarding the quality of tourist attraction at the baths in Kumaligon Village, Biau District, Buol Regency. The type of research used in this research is descriptive qualitative. In this study, data collection was carried out using 3 methods, namely Observation, Interview, and Documentation. The data sources used in this study consisted of two kinds, namely primary data and secondary data. This research is to describe and describe the results of research into complete, systematic sentences and carry out discussions to obtain an understanding so that conclusions can be drawn. Based on the results of the research conducted, the author concludes that from the perception of the manager, namely the Youth, Sports, and Tourism Office, the Head of the Kumaligon Village Government and the person in charge of the area, as well as tourists and visitors state the need for special attention to aspects of attractions which include natural tourist attractions and artificial tourist attractions. , Accessibility indicators include access roads and tourist information, and Facilities indicators that include services, security, food stalls, and lodging in Kumaligon baths